ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS PERUSAHAAN PASCA IPO DENGAN ANALISIS MULTINOMIAL LOGIT - Almilia, Luciana Spica; Silvy, Meliza (Journal of Indonesian Economy and Business, 2003)
This research has a purpose to provide empirical evident about factors that affect firms status after IPO. The examined factors on this research are firm characteristics including financial ratio, industry structure, firmâs sensitivity to macroeconomic variables, underwriter reputation and ownership structure.The samples consist of 84 firms which had positive net income, positive equity book value and still listed until 2002; 24 firms which had negative net income from 2000 through 2001 and still listed; 48 firms which had negative net income and negative equity book value from 2000 through 2001 and still listed; and 19 firms which delisted from 1999 through 2002. Moreover, it is chosen by purposive sampling. The statistic method used to test on the research hypothesis is multinomial logit regression. Indirect method and direct method technique is used to gain a model that has the highest classification power in determination firms status after IPO.The result show that direct method had a higher classification power rather than indirect method. This research also indicate that firm characteristic include financial ratio, industry structure, firmâs sensitivity to macroeconomic variables, and underwriter reputation is a significant variables in determination firms status after IPOKeywords: financial distress, financial ratios, multinomial logit, macroeconomic variable